Pembangunan Aplikasi Pendaftaran Operasi Penderita Katarak (Studi Kasus: Rumah Sakit Larasati Pamekasan) - Nawfal Alim Fardana; Denny Sagita Rusdianto; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The administration or registration process in the health facilities is very important. Because the registration process that too long and has a long queue will be unsettling and make prospective patients feel unsafe. Cataract is one disease that always increases every year in Indonesia. Although the process of cataract surgery is quick, and the cost has been borne by the government, the current problem is the registration process at different health facilities. In addition, data of patients with cataracts in each area must be noted for easier in aiding patients with cataracts, especially people who can not afford and have no insurance. Therefore, this research is intended to make the registration system or data collection can be done portable (anywhere and anytime) that will help the patient in administrative matters, so that when patients come to health facilities can directly undergo surgery and treatment. The system to be built will take advantage of volunteers as users of the system, the volunteers will help the process of cataract data collection by traveling to areas far from health facilities. This system will consist of websites for admins and doctors and mobile apps for volunteers. All the needs that exist in the system is the result of elicitation with doctors who daily operate on cataract patients. This system has been tested by unit testing with whitebox method, integration testing with blackbox method, and validation testing with blackbox method.